Music Entertainment at Islamic Wedding Feasts (Walimatul ‘Urs): Implications for Muslim Family Understanding in Indonesia - Fatimah Fatimah; Akmaluddin Syahputra; Imam Yazid (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the practice of musical entertainment in the implementation of walīmatul ‘urs and its implications for the understanding of Islamic law among Muslim families in Ujung Padang District, Simalungun Regency. The research uses a qualitative approach with field research through observation, interviews, and documentation techniques involving various informants, including wedding organizers, religious leaders, customary leaders, community members, and local youth. The results of the study show that forms of musical entertainment in walīmatul ‘urs consist of traditional music (rebana and hadrah), modern music (single organ and keyboard), as well as vocal entertainment such as religious and popular songs. These practices reflect the integration of social and religious values through a negotiation process between entertainment needs and adherence to Islamic norms. In addition, there is a spectrum of understanding of Islamic law among Muslim families, which is divided into two main tendencies, namely the view that allows with conditions and the view that is more restrictive. These differences are influenced by factors such as age, level of religious education, and social pressure. Furthermore, the practice of musical entertainment in walīmatul ‘urs has implications for the formation of an understanding of Islamic law that is contextual, adaptive, and dynamic. Tensions between custom (‘urf) and Islamic law (sharia) are also found, but are generally resolved through mechanisms of compromise and adjustment. This study asserts that the understanding of Islamic law at the family level is not static, but is formed through interactions between normative texts and socio-cultural practices. These findings contribute to the development of studies in Islamic law and the sociology of religion, particularly in understanding the dynamics of religiosity among Muslim communities in the local context.